Deutscher Weiterbildungsatlas - Martin, Andreas; Schömann, Klaus; Schrader, Josef; Kuper, Harm (Theorie und Praxis der Erwachsenenbildung, 2015)
"The study presents a cartographic overview of the offering of and demand for adult education in Germany. The authors have developed indicators from a variety of data sources, which allow an extensive and detailed view of the participation in adult education. With a view of the regions as reference frame, trend influences are developed and factors for adult education advantages and disadvantages are made visible. Some regions show abnormalities in the adult education behaviour. Results of regional case studies show that there are conductive as well as inhibiting factors for adult education opportunities. Here, the differences in adult education behaviour with regards to regionally varying levels and offers of further education become apparent."